2016
DOI: 10.1111/geob.12096
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Social Mix and Adults' Income Trajectories: Longitudinal Evidence from Stockholm

Abstract: We investigate the relationship between neighborhood income composition and income trajectories of adults, employing annual panel data from Stockholm over the 1991–2008 period and multiple measures of neighborhood income mix. We advance the human geography literature in three ways by quantifying neighborhood effects that: (1) are unusually precise due to our large sample size; (2) are arguably causal and unbiased due to the econometric techniques employed; (3) are potentially heterogeneous, varying according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 128 publications
(116 reference statements)
2
10
0
2
Order By: Relevance
“…Most of these studies find evidence of neighbourhood effects (there are however also examples of studies finding no effects at all; see [19, 20, 21]). Studies have also found neighbourhood effects to vary by individual characteristics [22, 23], spatial scale [24, 25] and length of exposure to certain neighbourhood types [23, 26, 27].…”
Section: Neighbourhood and Family Effectsmentioning
confidence: 99%
“…Most of these studies find evidence of neighbourhood effects (there are however also examples of studies finding no effects at all; see [19, 20, 21]). Studies have also found neighbourhood effects to vary by individual characteristics [22, 23], spatial scale [24, 25] and length of exposure to certain neighbourhood types [23, 26, 27].…”
Section: Neighbourhood and Family Effectsmentioning
confidence: 99%
“…For employed household heads moving to a new neighbourhood, a change in their income can be caused primarily by the aforementioned social mechanisms, but also by a number of other neighbourhood characteristics. In their study of the influence of neighbourhood social mix on Stockholm's inhabitants' income, Galster et al (2016) describe the potential influence of local crime levels, institutional resources and job accessibility, widely studied in the literature. Neighbourhood average income tends to be a good proxy for these characteristics because of local self-reinforcing processes of spatial inequality-for example, well-connected neighbourhoods tend to have more expensive dwellings, which attracts richer inhabitants, who further profit from the easy access to jobs and services (Toft & Ljunggren, 2016).…”
Section: Neighbourhood Effects On Income and Income Changementioning
confidence: 99%
“…Ten aanzien van de intensiteit moet nog worden opgemerkt dat in Stockholm ook buurten met meer dan 40 procent lage inkomens meestal nog sterk gemengd zijn. In het buurttype dat gedomineerd wordt door lage inkomens vinden we gemiddeld 59 procent huishoudens met lage inkomens, maar ook nog altijd 28 procent met middeninkomens en 13 procent met hoge inkomens (Galster, Andersson & Musterd, 2016).…”
Section: Figuur 1 Sterke Concentraties (> 70%) Van Amsterdammers Met Nederlandse (Rood) Respectievelijk Niet-westerse Achtergrond (Blauw)unclassified